How to Effectively Identify Patients With Rifampin-Resistant Tuberculosis in China: Perspectives of Stakeholders Among Service Providers - Hua, Qianhui; Xu, Hong; Chen, Xinyi; Pan, Junhang; Peng, Ying; Wang, Wei; Chen, Bin; Jiang, Jianmin (Frontiers in Public Health, 2021)
To evaluate China’s current rifampin-resistant tuberculosis (RR-TB) screening strategy from stakeholders’ perspectives, the perceptions, attitudes, and interests of 245 stakeholders from three eastern, central, and western China provinces on RR-TB screening strategies, were investigated through stakeholder survey and interview. The attitudes towards three RR-TB screening strategies were statistically different: inclination to choose who to screen (Z=98.477; P<0.001), funding for rapid diagnostic technology screening either by reimbursed health insurance or directly subsidized financial assistance (Z=4.142, P<0.001), and respondents' attitude during RR-TB screening implementation levels (Z=2.380, P=0.017). In conclusion, RR-TB screening scope could be expanded by applying rapid diagnostic technologies. Provinces with different economic status could adjust their screening policies accordingly.